Characteristics and Prognostic Value of Tertiary Lymphoid Organs in Membranous Nephropathy: A Retrospective Study - Wang, Zu-feng; Cheng, Yi-chun; Li, Yue-Qiang; Liu, Liu; Ge, Shu-Wang; Xu, Gang (Frontiers in Medicine, 2022)
Background: Tertiary lymphoid organs (TLOs) play an essential role in the inflammation of the kidney. The clinical association between TLOs and membranous nephropathy (MN) is not clear yet. Methods: MN Patients with the histologic diagnosis in Tongji hospital from July 19, 2012 to September 26, 2019 were included in this study. TLOs in renal biopsy tissues were detected by periodic acid–Schiff-stained and immunohistochemistry. Correlations of TLOs and clinical features of MN patients were evaluated by logistic regression. Kaplan-Meier analysis was used to examine the relationship of TLOs and remission of proteinuria. Results: 442 MN patients were included in this study, the average age of them was 46.4 years old, and 58.8% were male. Moreover, 33.0% of MN patients had TLOs in this study. The median value of proteinuria among MN patients with TLOs was 4.9g/24h and much greater than no-TLOs ones. Moreover, patients with TLOs had higher serum creatinine, lower serum albumin and higher uric acid. The severity of clinical features among MN patients aggravated with the increase of the grade of TLOs. In addition, patients have TLOs were more likely to be positive of anti-phospholipase A2 receptor autoantibodies. Meanwhile, patients without TLOs showed significantly higher complete remission and total remission of proteinuria. Conclusion: In this study, we found that TLOs were common among MN patients. Moreover, MN patients with TLOs showed a worse clinical manifestation and outcome compared with patients without TLOs.